Cross-Border Trade in the Pre- and Post-Pandemic Environment - United Nations Conference on Trade; Development (United Nations, 2022)
Since 2016, UNCTAD has been working to support women in informal cross-border trade in sub-Saharan Africa, carrying out analytical, capacity-building and policy advocacy activities. This report describes the results of an impact assessment of the capacity-building activities that UNCTAD conducted in Malawi, the United Republic of Tanzania and Zambia during 2019-2021. The capacity-building activities consisted of a 6-day training programme on trade rules and procedures, and entrepreneurship skills building, and were aimed at small-scale and informal cross-border traders, mainly women. This report assesses the impact of UNCTAD training programme on former participants, and looks at issues such as familiarity with trade rules, customs procedures and trader rights and obligations; enhanced use of official border posts; business resilience and adaptation; business formalization; and understanding of COVID-19 measures. It draws evidence from Malawi, the United Republic of Tanzania and Zambia, taking into consideration cross-border trade in the pre- and post-pandemic environment. Finally, it presents four case studies.